Lexical repetition and its impact on achieving textual coherence in the dialogue of the prophets (Noah, Hood, Saleh) with their people - Shimal khudhur Abdulrahman (Zanco Journal of Humanity Sciences)
This study deals with one of the means of lexical consistency, which is (repetition), which has a prominent role in achieving textual coherence in a dialogue of the prophets (Noah, Hood, Saleh) with their people. From this perspective, we studied repetition of its four types (complete, partial, synonymous, general words) as a way to highlight the textual coherence between a dialogue of one prophet with his people, or between two dialogues of the two prophets and sometimes between the dialogues of the three mentioned prophets, the study reached the conclusion that: The repetition of the four types of words mentioned has the ability to cohesion the parts of the dialogic text in the dialogue of the prophets (Noah, Hood, Saleh) with their people in the Holy Qur’an.